The TPACK model in the teaching of Chemical Stoichiometry - López Cevallos , Franklin Ernesto; Tulcán Benavides , Fabián Laureano; Lascano Rivera, Samuel (SATHIRI, 2025)
Contemporary education integrates information and communication technologies in the pedagogical process; an alternative to integrate these aspects is the technological, pedagogical and content knowledge model. The objective of this study was to propose the use of TPACK in teaching Chemical stoichiometry to second-year high school students at the Tulcán Educational Unit. The TPACK model, its components and the parameters involved in the teaching-learning process of Chemistry were addressed. A quasi-experimental design was used with a quantitative, exploratory, correlational and transversal approach. There was an experimental group of 28 students and a control group of 24. A pretest and a posttest were applied to analyze the statistically significant differences when using the model in teaching. Validated instruments were used at a quantitative level using Cronbach's Alpha coefficient and at a qualitative level with the opinion of experts in education and technology. The results showed that the use of the TPACK model led to improvements in student performance, with a bilateral significance, lower than the significance level of 0.05 (alpha). A proposal was generated based on the use of technological tools for teaching Chemical stoichiometry. The possibility of replicating this approach in a greater number of Chemistry topics or other subjects in the future is suggested.
Keywords: TPACK Model; Teaching; Learning; Zone of Proximal Development; Stoichiometry